Ang daan patungong Kalimugtong - De Guzman, Mes; Almoete, Joey; Bangsi-il, Analyn; Bassig, Jay; Cine Larga (Firm). ([Place of production not identified] Cine Larga, 2005)
A brother and sister trek over mountains, cross rivers, and walk over a bridge between cliffs to and from school. After school, they take care of pigs and their ill grandfather in bed. At night they dine with their older brother and do homework. Looks like a simple life which has nothing to lose, but it has. When news arrives that the mine is collapsed where their older siblings have been working to support them, the family falls in danger of starvation. The repetition of daily life mixes with dramatic tension which gradually rushes to them.--Pusan International Film Festival
Music by Bernard "Nio" Manzano; cinematography by Albert Banzon.
Joey Almoete, Analyn Bangsi-il, Jay Bassig.
DVD
In Tagalog
Keywords: Drama